Diseño de un modelo semiótico para el análisis de interfaces socio estatales (ISE) de entornos web - Gómez Gómez, Jhon Mario (2023)
The following research sets out the design of an analysis model that allows evaluating the significant dimensions of socio-statal interfaces (ISE by its Spanish acronym), specifically those interfaces that move around the web. We propose the development of a methodological analysis model based on Peircean semiotics that allows us to address, deeply and extensively, the socio-statal interface sign in its firstness, secondness, and thirdness. And, from there, contribute to the heuristic power of the evaluation and analysis methods present in the user, such as the UX (User Experience) methodology or the UCD (User-Centered Design) methodology. In short, we believe that a logical-operative research field as the Peirce Semiotics can significantly update the ways we approach and evaluate these types of interfaces. This work will evaluate the concept of the socio-statal interface (ISE) itself in terms of meaning-making, and from there, propose an analysis method that allows us to expand its understanding beyond the simple ponderation of its operative function. And thus, inquire into its ways of meaning-making in the proposed political negotiations between the State and its people (Roberts, 2001).